Inherited predisposition to breast cancer - Eccles, Diana (Henry Stewart Talks, 2014)
Breast cancer incidence around the world, Roles of inherited susceptibility and environment in cancer, High and low risk inherited susceptibility genes, The BRCA1 and BRCA2 susceptibility genes, The rare high risk gene TP53, Genetic testing: current uses and future potential